Morphology and phylogeny of Teratoramularia rumicis—a new foliar pathogen of Rumex crispus from India and diversity of Ramularioid complex on Rumex spp. - Verma, Sanjeet Kumar; Kushwaha, Prakash; Yadav, Sanjay; Singh, Raghvendra (Phytotaxa, 2021)
Teratoramularia rumicis, a new hyaline anamorphic foliicolous hyphomycetous fungus was discovered on living leaves of medicinally important plant Rumex crispus (Polygonaceae) is described and illustrated. It is an obligate foliar pathogen that causes silvery white foliar disease. It is the first report of Teratoramularia from India. This species is compared with closely related species of Teratoramularia and species of Ramularioid complex along with dematiaceous cercosporoid forms reported on the same host genus and family. The phylogeny of this species has been inferred from combined 28S nrRNA gene (LSU) and internal transcribed spacer regions and intervening 5.8S nrRNA gene (ITS) of the nrDNA operon.